Market preferences on archives and records management distance training - Altre, Alnera Mia DG (School of Library and Information Studies, University of the Philippines Diliman, 2017)
This study explored on the market preferences on archives and records management distance training. The study sought to understand the environmental influences and how these affect the market preference on the methods of delivery and willingness to pay (WTP). It was also directed in achieving familiarity with the details, settings, and concerns of the target market for archival distance training. Furthermore, this study also attempted to determine the feasibility of this study in the future. A qualitative method of research was used in gathering evidences. Questionnaires were given to select respondents from Regions I, II, and the Cordillera Administrative Region. Further interviews were also conducted to clarify answers given to questions on the questionnaire and to ascertain that the answers are precise. The research used a small quantity of sample size respondents hence, the use of the said method. The study revealed that a number of people in the target market has little knowledge with distance training ; the benefits and advantages it has. But the most preferred method of delivery appeared to be video conferencing and the market's willingness to pay ranges from P300.00 to P7,000.00.